PERAN SUAMI DALAM MEMBERIKAN DUKUNGAN MORIL PERSIAPAN PERSALINAN DI PUSKESMAS PLERET BANTUL - Mahmudah, Happy; Barokah, Liberty (MEDIA ILMU KESEHATAN, 2016)
Background: Husband’s role is very crucial in supporting their wives in a process of delivery. The lack of a husband's role will lead to low participation in caring activities during the pregnancy, childbirth, and postpartum period. Husband should be given knowledge about birth preparedness, which includes the planning of laborand preparing for a decision-maker in a case of emergency. Objective: To determine the role of husband in providing moril support to their wives in labor process at Pleret Bantul Puskesmas. Methodology: This research was descriptive quantitative, conducted at Pleret Bantul Puskesmas in 2015. Thirty-two respondentswere involvedassamplesby total sampling technique. Results:The husband's role in providing moril support on the expected date of birth was mostly high (87.5%). The husband's role in providing moril support during the pregnancy check was high (50.0%). The husband's role in providing moril support during the process of delivery is mostly high (81.3%).The husband's role in providing moril support in planning the labor process was high (59.4%). Conclusion:The role of the husband in providing moril support to their wives in labor process at Pleret Bantul Puskesmas washigh (59.4%). Keywords: Husband’sRole, Moril Support, Childbirth